Determination of Safe Concentration of Non-Carcinogenic Toluene in Surabaya Printing - Ahmad Rido'i Yuda Prayogi; Dr. Abdul Rohim Tualeka; Dr. Ahsan Ahsan; Dr. Pudji Rahmawati; Dr. Syamsiar S Russeng; Indri H Susilowati (Berita Kedokteran Masyarakat (BKM), 2020)
Aims: The research objective is to determine the safe concentration of non-carcinogenic toluene in Surabaya printing. Methods and Material: The research design used was observational analytic, cross sectional research design with a quantitative approach. The research location is a printing press in Surabaya. Total population was 37 workers, the study sample was taken using the accidental sampling method with a total sample of 30 respondents. The formula for determining the concentration of toluene non carcinogen intake is (CxRxtExfExDt): (Wbx30x365). Results:  The concentration value of toluene exposure is greater than the standard set by labor regulations No. 5 of 2018 by 0.2 ppm. A total of 10% of workers falls under normal category, 73% above normal category and 27% below normal category. Conclusions: The concentration of toluene exposure in Surabaya printing area is above normal with a concentration of 0.2 ppm and this is considered normal.